2019
DOI: 10.1097/md.0000000000015441
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of clinical features and prognosis of edaravone in the treatment of paraquat poisoning

Abstract: To observe whether edaravone can protect organs and inhibit pulmonary fibrosis in patients with paraquat poisoning and to provide a method for clinical intervention for paraquat poisoning. Forty-four cases of paraquat poisoning were collected from March 2011 to December 2017 in our hospital. Eighteen cases from March 2011 to November 2013 did not receive edaravone treatment and were considered the control group, and 26 cases from January 2014 to December 2017 were treated with edaravone and were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The mechanisms might involve scavenging free radicals, inhibiting lipid peroxidation, inhibiting inflammatory factors, protecting renal mitochondria, inhibiting cell apoptosis and reducing oxidative stress 13 14 24. Similarly, it has also been found in clinical studies that edaravone might play a protective role in the kidney by exerting antioxidant stress and inhibiting inflammatory levels in patients with paraquat poisoning 25 26. A study found a negative correlation between edaravone use and AKI in 5689 patients with acute ischaemic stroke,26 which was consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
“…The mechanisms might involve scavenging free radicals, inhibiting lipid peroxidation, inhibiting inflammatory factors, protecting renal mitochondria, inhibiting cell apoptosis and reducing oxidative stress 13 14 24. Similarly, it has also been found in clinical studies that edaravone might play a protective role in the kidney by exerting antioxidant stress and inhibiting inflammatory levels in patients with paraquat poisoning 25 26. A study found a negative correlation between edaravone use and AKI in 5689 patients with acute ischaemic stroke,26 which was consistent with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, the use of vanillin has been proposed to reduce kidney damage and cisplatin-induced nephrotoxicity [30]. Similarly, the use of EDA is also envisioned to prevent cisplatin-induced acute kidney injury [31] and as a reno-protective drug in diverse pathological situations [32][33][34]. Both EDA and vanillin can be useful protecting agents to reduce and prevent kidney diseases, but our work strongly suggests that the two compounds shall never be combined and used simultaneously, due to the high risk of adducts formation.…”
Section: Discussionmentioning
confidence: 99%
“…Atorvastatin, a lipid lowering drug, has been recently shown to attenuate PQ-induced cardiotoxicity in a rat model through similar mechanisms [ 42 ]. The results from a retrospective study demonstrated that edaravone, a free radical scavenger with an anti-inflammatory effect, protected the kidneys and liver but did not reduce pulmonary fibrosis and survival rate in patients with paraquat poisoning [ 43 ]. Currently, finding an effective strategy for the treatment of PQ-induced toxicity is attracting the attention of researchers.…”
Section: Discussionmentioning
confidence: 99%